Assessing the Role of Family Support in Heart Failure Care: A Quantitative Perspective - Alsa Cicin Sejatika; Beti Kristinawati (Indonesian Journal of Global Health Research, 2026)
Heart failure causes functional impairment and impacts patients' quality of life. A family-centered approach involving families as partners in care is an effective strategy for improving patients' quality of life. Objective: This study aims to identify the role of families in implementing family-centred care for heart failure patients. A quantitative descriptive design involving 317 families of heart failure patients. Purposive sampling based on predetermined criteria was applied in this study.  The Family Centered Care Assessment of Family (FCCA-F)  instrument was used to identify the role of families in decision-making, providing support, and family-to-family and peer support. Data analysis was performed using computer software. Analysis to present data used descriptive statistics. The results showed that the domain of the role of families in decision-making and the support provided by the immediate family were "relatively strong" in the majority of cases (57.1% and 63.1%). This indicates the active involvement of the immediate family in the care and support process for heart failure patients. However, most (70.3%) of the family-to-family and peer support domain  results were "weak." This finding indicates that initiatives to connect patients' families have not been fully realised. These findings show that the family's role in decision-making and supporting heart failure patients is decisive, improving quality of life and therapy compliance. However, the family-to-family and peer support domains are still weak, requiring the development of support group initiatives to optimise patient care and quality of life.